2008
DOI: 10.1021/ie8006825
|View full text |Cite
|
Sign up to set email alerts
|

One-Part Geopolymer Mixes from Geothermal Silica and Sodium Aluminate

Abstract: In geopolymer technology, silicate solutions are frequently used as alkali activators to dissolve the solid aluminosilicate precursor and aid in binder formation. These corrosive and often viscous solutions are not user-friendly and would be difficult to use for bulk production. Developing geopolymers as a one-part mixture ("just add water"), similar to Portland cement, increases their commercial viability. Here, for the first time, the geopolymer system consisting of geothermal silica and solid sodium alumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(110 citation statements)
references
References 37 publications
6
99
1
4
Order By: Relevance
“…A new approach is the so-called ''one-part'' mixes [10] which are produced by a different synthesis route. One-part geopolymers contain the activator in solid form and therefore only water has to be added to initiate hardening, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new approach is the so-called ''one-part'' mixes [10] which are produced by a different synthesis route. One-part geopolymers contain the activator in solid form and therefore only water has to be added to initiate hardening, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…By applying this approach, it is not necessary to store and handle highly alkaline waterglass or sodium hydroxide solutions, which avoids problems with carbonation and ageing of these solutions as well as problems with health and safety issues. This can provide a higher social and economic acceptance of these new binder materials [10,11]. Different ways to synthesize one-part geopolymers have been described [10,[12][13][14], and microstructural, mechanical and rheological studies are reported [10,[12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers for infrared spectroscopy study were synthesised using a 'onepart' (just add water) procedure [10]: solid washed geothermal silica (96% SiO 2 , from the Cerro Prieto geothermal power station, Mexico) and reagent-grade sodium aluminate (Aldrich) were blended to give the desired Si/Al ratios, and then mixed with water at a molar ratio of H 2 O/Na 2 O = 12. ATR-FTIR spectra of onepart mix geopolymers were collected using a Varian FTS 7000 FT-IR spectrometer, with a Specac MKII Golden Gate single reflectance diamond ATR attachment with KRS-5 lenses and heater top plate.…”
Section: Methodsmentioning
confidence: 99%
“…Bands at 1060 cm -1 are assigned to stretching of Si-O-Si bonds at the surface of the unreacted silica particles [15], and bands at 1100, 800 and 475 cm -1 relate to stretching, bending and rocking of the Si-O-Si bonds within the network of the [10] unreacted particles of geothermal silica [16]. Bands at 545, 625 and 700 cm -1 are related to vibrations in the unreacted solid aluminate [17].…”
Section: Time-resolved Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation